Pembentukan kalium sulfat dari belerang, kalium karbonat, dan oksigen dengan proses satu langkah ditinjau dari segi kinetika - MULJADI, Edi (Universitas Gadjah Mada, 2001)
The need for Potassium sulfate in Indonesia increases steadily, and almost all of this commodity must be imported. Efforts to produce potassium sulfate had been taken, but they were not feasible if applied in industry. This research was intended to find a simple process using raw materials available in Indonesia. One of the possibilities is to produce potassium sulfate continuously by oxidizing sulfur suspended in potassium carbonate solution with oxygen in one step. The process was performed in a vertical tube reactor provided with slanted baffles. Sulfur suspended in potassium carbonate solution was fed continously from the top of the reaFtor, and oxygen was bubbled from the bottom. The process was continued until steady state condition was reached. Then, the concentrations of carbonate, thiosulfate, and sulfate were determined. Potassium polysulfide and sulfuric acid were not found in the liquid product. Therefore, both compounds were just formed as intermediate products. By varying the gas flow rate the reaction occured in the liquid fase was proved. The overall rate of reaction was controlled by mass transfer and chemical reaction. This was confirmed by the values of activation energy of reaction between sulfur and potassium carbonate cal/gmole), and oxidation of solution (3435.9 potassium thiosulfate to potassium sulfate (5156.5 cal/gmole), which were less then 10000 cal/gmole. Besides, the effects of sulfur particle diameter, initial potassium carbonate concentration, sulfur content of the suspension, oxygen conentration, and total pressure, also proved that the reaction occured in the liquid fase and controlled by both mass transfer and chemical reaction. Chemical reaction rate constant and mass transfer coefficient were affected by all variables logarithmically, but exponentially by temperature.